Evaluation of high-pressure as a novel non-thermal extraction technology to obtain extracts with improved biological activities - Moreira, Sílvia Alexandra Monteiro (2020)
Both stinging nettle and winter savory are both perennial herbs usually found in the Mediterranean area, being traditionally used as medicinal herbs against several ailments due to the biological properties associated to their rich chemical composition. The first part of the present work aimed to evaluate the effect of high pressure assisted extraction (HPE) and its optimization by response surface methodology using a central composite face centered design in order to obtain extracts with high content of bioactive compounds and improved bioactivities. The effect of pressure level, extraction time, and solvent (ethanol:water) concentration was evaluated, as also the impact of HPE on total phenolics (TPC), flavonoids, pigments, and antioxidant activity. Results showed that experimental data could be well fitted to second-order polynomial mathematical models. For stinging nettle leaves extraction process, the optimal conditions for maximization of extraction yield, TPC, and antioxidant activity were 200 MPa, 10.2-15.6 min, and 0% ethanol (aqueous extracts); while for winter savory leaves, the models predicted optimal conditions ranging from 200-500 MPa, extraction time 1-20 min, and ethanol concentration 0-70%. In comparison with control extraction at atmospheric pressure, HPE allowed to increase the extraction yield about 50.5%; TPC about 84.4%; and antioxidant activity about 77.7% for stinging nettle extracts; and an increase of about 40% for all compounds, 29, 48, and 70% for antioxidant activity by FRAP, DPPH and ABTS assays, respectively, for winter savory extracts. In the second part of this work, the biological properties and toxicity of the controls and the optimized extracts from both herbs were studied. The studied extracts were obtained at pressure levels ranging from 200 and 500 MPa, 10-20 minutes, 0-70% ethanol. Each extract was characterized for their individual compounds profile and different biological properties, such as antioxidant activity, pro-oxidant activity (DNA degradation capacity), as also its antimicrobial, antibiofilm, and antihypertensive activities. The extracts cytotoxicity and antiproliferative effect on human tumour cell lines were also evaluated. For stinging nettle, the extracts obtained at 200 MPa, 10 min, 35 and 70% ethanol were the ones presenting higher concentrations of TPC and flavonoids, such as chlorogenic acid, isoferulic acid, and rutin, being also the ones with better results concerning all the studied biological activities; while for winter savory, the extract obtained at 348 MPa, 20 min, 35% ethanol showed to be the most interesting, since it presented a high concentration of individual phenolic compounds, such as tuberonic acid glucoside, rosmarinic acid, salvianolic acid A. HPE extracts showed potential antioxidant and DNA protective activities, since they were able not only to cause fewer damages in the DNA molecule than the controls, but also were able to protect it against the damage caused by oxidative stress. Concerning the cytotoxicity, it was observed that HPE extracts, in a concentration of 0.5 and 1.0 mg/mL, were not harmful to HT29 cell lines, but the control extracts at higher concentration (>1.0 mg/mL) showed that the extracts can slightly reduce the metabolic activity. Finally, all the extracts showed to inhibit the viability of three cancerous cell lines (>2.0 mg/mL for Caco-2, HeLa, and TR146), indicating that these extracts may present a potential antitumoral activity. The last part of this work aimed to evaluate the effect of supplementation of carrot juice with winter savory leaves extract, on the final juice characteristics, after storage for 15 days under refrigeration. Supplemented juices presented lower microbial counts than the non-supplemented ones, and, generally, did not present significant changes (p>0.05) in pH or colour. Concerning the total phenolics and total flavonoids, as well as antioxidant activity, the values were generally higher in supplemented juices, which was proven by the high correlation found between total phenolics content and antioxidant activity by ABTS and FRAP assays.